Adaptive event-based robust passive fault tolerant control for nonlinear lateral stability of autonomous electric vehicles with asynchronous constraints. (August 2022) - Zhao, Jing; Wang, Xiaowei; Liang, Zhongchao; Li, Wenfeng; Wang, Xianbo; Wong, Pak Kin
Abstract: This work solves the robust passive fault-tolerant control problem for autonomous electric vehicles based on an adaptive event triggered mechanism. Firstly, given the system uncertainties from the tire dynamics and the longitudinal speed, the T–S fuzzy model method is used to approximate the vehicle lateral dynamics. Secondly, taking the communication constraints caused by band-limited networks into account, an adaptive event-triggered scheme is introduced in the process of the control design. Moreover, the asynchronous constraint of the weight function between the controller and system is considered. Thirdly, considering that the actuator faults are inevitably encountered in the control system, a robust passive fault-tolerant control method is proposed to improve vehicle performances. Finally, simulations are carried out to illustrate the effectiveness and robustness of the proposed approach. Highlights: A fuzzy vehicle dynamic model is constructed with asynchronous constraints. An improved AET mechanism is designed to reduce the transmitted number of signals. The actuator faults are described by a polytope with finite vertices. A new Lyapunov function is developed to solve the problem of limited delay range.